Analisis Penerapan Enterprise Risk Management Terhadap Risiko Produk Halal UMKM Juragan Dimsum Kota Medan - Rumenta Sinaga, Ernita; Pandiangan, Norenty Elisabet; Simbolon, Hotman Pangihutan (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2024)
This research discusses the application of enterprise risk management (ERM) to the risks of halal products faced by SMEs in Juragan Dimsum, Medan City. MSMEs play an important role in the national economy, especially in Indonesia, and the culinary industry is the main sector among MSMEs. Through steps such as risk identification, mitigation, monitoring and employee training, Juragan Dim Sum MSMEs can ensure compliance with halal standards when processing dimsum raw materials. This research uses a qualitative approach using interview, observation and documentation techniques to provide an overview of how ERM can help small and medium businesses better manage the risks of halal products. By implementing ERM, small and medium businesses can effectively identify and manage risks, achieve business goals, and increase consumer confidence in the halal products they produce.